Circular RNAs: roles in hepatocellular carcinoma immune regulation, implications in immunotherapy, and prospects for clinical translation - Chen, Yifan; Zhao, Jiayi; Pu, Rui; Fu, Chao; Li, Zishuai; Yin, Jianhua; Cao, Guangwen (Frontiers in Molecular Biosciences, 2026)
Circular RNAs (circRNAs) are emerging as pivotal regulators within the tumor immune microenvironment (TIME) of hepatocellular carcinoma (HCC). Despite the transformative role of immunotherapy, its efficacy remains limited by primary and acquired resistance, a challenge not fully addressed by current research. This review uniquely synthesizes the latest evidence to delineate how specific circRNAs orchestrate immunosuppression in HCC through two interconnected axes: (1) by directly modulating the function and polarization of key immune cells (e.g., T cells, NK cells, macrophages), and (2) by interfering with core immune-related signaling pathways (e.g., NF-κB, MAPK, Wnt/β-catenin). We critically examine how these mechanisms collectively fuel immune evasion and confer resistance to immune checkpoint inhibitors. Moving beyond mechanism, we further explore the dual translational potential of circRNAs: as stable, minimally invasive diagnostic/prognostic biomarkers and as novel therapeutic targets via RNA interference or circRNA-based vaccine strategies. By connecting fundamental molecular insights to clinical challenges, this review provides a cohesive framework for understanding circRNA-driven immunomodulation in HCC and highlights promising avenues for overcoming immunotherapy resistance.